2017
DOI: 10.4103/ejd.ejd_27_17
|View full text |Cite
|
Sign up to set email alerts
|

Dental students' knowledge of medication-related osteonecrosis of the jaw

Abstract: Objectives:The aim of this study was to evaluate and assess knowledge and attitude of dental students about medication-related osteonecrosis of the jaw (MRONJ), to optimize future training programs in this field.Materials and Methods:A cross-sectional study was administrated. Ninety-eight participants agreed to complete an anonymous questionnaire. It was divided into two sections: the first section was about general information such as interviewer's gender and date of birth; the second section included questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
28
2
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 26 publications
8
28
2
11
Order By: Relevance
“…10 The first source of information on BAONJ in our study as well as the study of Rosella et al 18 was university, followed by reading scientific papers, but the authors state that even though ninety-nine percent of dental students in their study declare to know BPs and identified the importance to report the use of BPs, only one fourth of 4-year students and one third of 6-year students knew the correct definition of BAONJ and half of the students did not recognize any active principle or commercial name of BPs, which shows some alarming educational gaps. 18 3. We have noticed a tendency for better knowledge about the problem of doctors with shorter length of service (up to 4 years).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…10 The first source of information on BAONJ in our study as well as the study of Rosella et al 18 was university, followed by reading scientific papers, but the authors state that even though ninety-nine percent of dental students in their study declare to know BPs and identified the importance to report the use of BPs, only one fourth of 4-year students and one third of 6-year students knew the correct definition of BAONJ and half of the students did not recognize any active principle or commercial name of BPs, which shows some alarming educational gaps. 18 3. We have noticed a tendency for better knowledge about the problem of doctors with shorter length of service (up to 4 years).…”
Section: Discussionmentioning
confidence: 88%
“…17 Rosella et al reported that dental students' knowledge about how invasive dental treatment might be carried out in patients under therapy was not adequate. 18 These knowledge gaps may lead to situations where patients receiving intravenous BP are treated too invasively and pa-tients receiving low doses of oral bisphosphonates are not treated correctly. 17 4.…”
Section: Discussionmentioning
confidence: 99%
“…14% would perform surgical procedure, 30% would perform surgical procedure only if AM was discontinued, 56% would not perform any surgical procedure and refer the patient. In a similar study, Rosella et al found conflicting results regarding the recognition of AM and insufficient knowledge to provide a safe dental treatment [5]. Although 94% of the participants reported that it is important to recognize patients under treatment, only 39% knew how to treat patients taking oral AM for less than four years and 44% did not know how to treat those taking oral AM for more than four years.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the almost 10 years, an increasing number of cases of BP-related ONJ have been published [16][17][18][19] since the last publication of the AAOMS position paper on BRONJ, which was based on multicentric evidence from specialists and approved by the AAOMS Board of Trustees [7]. According to Rosella et al, a high level of knowledge is needed to reduce the incidence of BP-related ONJ by preventing it and improving its treatment [5]. Saad et al also highlighted that a higher level of knowledge on AM among oral surgeons provides a better quality treatment [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation